Design in modular construction - Lawson, R.M; Ogden, Raymond; Goodier, Chris I. (Chris Ian) (CRC Press, 2014)
Modular construction can dramatically improve efficiency in construction, through factory production of pre-engineered building units and their delivery to the site either as entire buildings or as substantial elements. The required technology and application are developing rapidly, but design is still in its infancy. Good design requires a knowledge of modular production, installation and interface issues and also an understanding of the economics and client-related benefits which influence design decisions. Looking at eight recent projects, along with background information, this guide gives you coverage of: generic types of module and their application; vertical loading, stability and robustness; dimensional and spacial planning; hybrid construction; cladding, services and building physics; fire safety and thermal and acoustic performance; logistical aspects--such as transport, tolerances and safe installation. A valuable guide for professionals and a thorough introduction for advanced students.